Border Futures - Zukunft Grenze - Avenir Frontière: The future viability of cross-border cooperation - Karina Pallagst; Andrea Hartz; Beate Caesar (Verlag der ARL - Akademie für Raumentwicklung in der Leibniz-Gemeinschaft, 2022)
What current discourses are relevant for border areas? What opportunities for and obstacles to integrated territorial development arise from the specific situation of border regions? How can these be utilised or overcome in a goal-oriented way? These questions were central to the discussions of the Border Futures working group. Border regions like the Greater Region1 or the Trinational Metropolitan Region of the Upper Rhine extend far beyond the immediate border area. While institutional structures of cooperation can be perpetuated through agreements and organisations, there is a lack of instruments which cross-border cooperation structures can deploy in response to changing situations. Cross-border cooperation faces new challenges from increasing cross-border interactions, processes of economic structural transformation, new energy policies in the national sub-spaces, and demographic change. Another factor is increasing spatial polarisation, which influences the further development and future viability of the affected border areas, and involves metropolisation issues in urban centres and the provision of public services in rural districts. Building on discussions of the Border Futures working group, this volume sheds light on cross-border cooperation in practice with recent research relevant to planning in border regions in the European context. The insights collected here are intended to be usable in the border areas within the territory of the Regional Working Group and should also contribute towards the broader specialist discourse on the further development of cross-border cooperation. Issues of sustainable cross-border governance, new spatial functions and new planning instruments play a role here, as do the possibilities provided by the current EU structural policy programming period for border areas.
urn:nbn:de:0156-409768; http://econpapers.repec.org/RePEc:zbw:arlaba:259407; http://econpapers.repec.org/RePEc:zbw:arlaba:259422; http://econpapers.repec.org/RePEc:zbw:arlaba:259420; http://econpapers.repec.org/RePEc:zbw:arlaba:259412; http://econpapers.repec.org/RePEc:zbw:arlaba:259421; http://econpapers.repec.org/RePEc:zbw:arlaba:259411; http://econpapers.repec.org/RePEc:zbw:arlaba:259424; http://econpapers.repec.org/RePEc:zbw:arlaba:259410; http://econpapers.repec.org/RePEc:zbw:arlaba:259425; http://econpapers.repec.org/RePEc:zbw:arlaba:259419; http://econpapers.repec.org/RePEc:zbw:arlaba:259423; http://econpapers.repec.org/RePEc:zbw:arlaba:259414; http://econpapers.repec.org/RePEc:zbw:arlaba:259405; http://econpapers.repec.org/RePEc:zbw:arlaba:259418; http://econpapers.repec.org/RePEc:zbw:arlaba:259406; http://econpapers.repec.org/RePEc:zbw:arlaba:259417; http://econpapers.repec.org/RePEc:zbw:arlaba:259415; http://econpapers.repec.org/RePEc:zbw:arlaba:259416; http://econpapers.repec.org/RePEc:zbw:arlaba:259409; http://econpapers.repec.org/RePEc:zbw:arlaba:259413; http://econpapers.repec.org/RePEc:zbw:arlaba:259408
Keywords: 710; cross-border cooperation; spatial planning; spatial development; border area; border region